2023
DOI: 10.6007/ijarbss/v13-i2/16351
|View full text |Cite
|
Sign up to set email alerts
|

Servant Leadership and Proactive Personality as Impetus for Teachers’ Organizational Citizenship Behaviour

Abstract: Transformation in the national education, a dynamic education environment, and limited resource capability do not allow schools to function effectively if teachers are solely working on their own tasks. Hence, the educational sector greatly depends on teachers who are willing to exhibit organizational citizenship behaviour which is discretionary behaviour beyond their own tasks. Particularly, this study aims to investigate the influence of servant leadership and proactive personality on organizational citizens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…Unlike several previous studies (Amir and Santoso, 2019;Aziz et al, 2018;Dixon, 2013;G € UÇEL and Begec, 2012;Harwiki, 2016;Mathur and Negi, 2014;Mostafa, 2014;Setyaningrum, 2017), this research did not show any significant relationship between servant leadership and OCB. One explanation for this finding may be that this research was conducted among volunteers at local churches.…”
Section: Servant Leadership and Organizational Citizenship Behaviorcontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike several previous studies (Amir and Santoso, 2019;Aziz et al, 2018;Dixon, 2013;G € UÇEL and Begec, 2012;Harwiki, 2016;Mathur and Negi, 2014;Mostafa, 2014;Setyaningrum, 2017), this research did not show any significant relationship between servant leadership and OCB. One explanation for this finding may be that this research was conducted among volunteers at local churches.…”
Section: Servant Leadership and Organizational Citizenship Behaviorcontrasting
confidence: 99%
“…Some researchers found that there was a direct relationship between SL and OCB (Amir and Santoso, 2019;Aziz et al, 2018;Dixon, 2013;G € UÇEL and Begec, 2012;Harwiki, 2016;Mathur and Negi, 2014;Mostafa, 2014;Setyaningrum, 2017). The literature reveals that there is a significant relationship between servant leadership and OCB (Amir and Santoso, 2019;Aziz et al, 2018;Dixon, 2013;G € UÇEL and Begec, 2012;Harwiki, 2016;Mathur and Negi, 2014;Mostafa, 2014;Setyaningrum, 2017); however, this has not been studied among volunteer employees. Based on the literature we hypothesize H3.…”
Section: Servant Leadership and Volunteer Attitudesmentioning
confidence: 99%
“…It means that leaders who implement the servant leadership approach can increase the OCB of the employees. The result of the research is compliance with (Mathur and Negi, 2014) revealed that SL gives a positive effect on OCB. On the contrary, Harwiki (2013) found different findings that SL does not give an effect on OCB.…”
Section: Servant Leadership On Ocbmentioning
confidence: 57%